Properties of melamine urea formaldehyde particleboard produced from Buluh Semantan (gigantochloa scortechinii) / Jamaludin Kasim, Abdul Jalil Ahmad and Shaikh Abdul Karim Yamani - Kasim, Jamaludin; Ahmad, Abdul Jalil; Yamani, Shaikh Abdul Karim (2006)
Single-layer melamine urea formaldehyde particleboard was produced using buluh semantan (Gigantochloa scortechinii). Sixty bamboo clums from I, 2 and 3 year-old bamboo was used in the study. In the manufacture of homogenous board, three different resin contents were applied; 8, 10 and 12% using three different particle sizes of 0.5-1.0, 1.0-2.0 and > 2.0 mm. One percent wax was added while no wax was used for the controlled boards. The results indicate that all the properties tested (except for IB) decrease significantly with age. All the mechanical properties increase, the physical properties is better with increase in the resin content. Particle size influence significantly the mechanical and physical properties of the particleboard produced. Wax addition decreases the mechanical properties but increases the dimensional stability of the particleboard.